DINAMIKA SUPERVISI DALAM MANAJEMEN BIMBINGAN DAN KONSELING SEKOLAH - Marsal Yunas Muliadi Hasibuan; Roiz Zulhadi; Dasril Dasril (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The aim of this research is to describe the dynamics of implementing guidance and counseling supervision management. The research method employed is literature review. Content analysis is used as the data analysis method. The research findings reveal that the implementation of guidance and counseling supervision experiences various dynamics such as mismatched qualifications of supervisors, inconsistency in conducting supervision, and lack of motivation and support in its implementation.